A web page for community pharmacists to improve continuity of care between hospital and ambulatory care. Issue 2 (12th March 2012) - Mattiuzzo, M.; Kaestli, L.-Z.; Guignard, B.; Wasilewski-Rasca, A.-F.; Fonzo-Christe, C.; Bonnabry, P.
Abstract : Background: In Switzerland, in the absence of a pharmaceutical service ensuring seamless care, treatment plans prescribed at hospital discharge may be difficult to understand and to validate for community pharmacists. Information sources on products and drug doses used in the hospital are often lacking. Continuity of care may be therefore disrupted. Purpose: To determine which information could be useful for community pharmacists to ensure seamless care and provided through a dedicated web page. Material and method: 1. Internet search (July 2009) of web sites from 43 hospitals (Switzerland 28, France 5, Canada 10) and evaluation of the available pharmaceutical information. 2. Survey of problems at hospital discharge observed by 9 students during their assistantship in community pharmacies (May 2009). 3. Creation of a web page on the internet site of the hospital pharmacy. Results: Of the 43 hospital web sites, 22 (51%) had a web page dedicated to their hospital pharmacy but only 9 (21%) (Switzerland 6, France 0, Canada 3) did contain pharmaceutical information like preparation and administration of drugs, or pharmacology data. No web page was specifically intended for community pharmacists. Problems observed by students at discharge were mainly related to manufactured or imported products and to knowledge of paediatric doses used in the hospital setting. A web page was created with information about the hospital pharmacy (i.e out-of-hours pharmaceutical services), protocols of manufactured products with stability data, information on imported drugs and useful pharmacological and medical information for the validation of prescriptions (i.e usual hospital paediatric drug doses). Conclusion: No web page specifically intended for community pharmacists has been found on the internet. A model has been created and published on the web site of the HUG pharmacy (http://pharmacie.hug-ge.ch/infos_prat/infos_officine.html ). Satisfaction of community pharmacists regarding the content of this web page and impact on seamless care should be evaluated in the future.